Modern Prospects of the Development of Military Vehicle Technology (The Peerian Journal, 2022)
It is not for nothing that the advanced approach in the field of civil protection is recognized by the international community among the great achievements we are making on all fronts. This article describes the modern prospects of the development of military vehicles in our country.